Pengaruh Pencemaran Kadmium Pada Air Sumur Untuk Minum Dan Memasak Terhadap Kesehatan Wanita Di Desa Bambe Kecamatan Driyorejo, Gresik - Sutrisno, Sutrisno; Budiyono, Budiyono (Jurnal Kesehatan Lingkungan Indonesia, 2004)
ABSTRACT Background : Cadmium is highly hazardous substance to human being. Some health disorders caused by cadmium are: anemia, tubular cell damage and bone tissue damage. The aims of this research to know the correlation between cadmium level of the water-table well and cadmium level in blood of  women living in Bambe Village. Methods : This research is an analytical observational study using comparative analysis with cross-sectional design. The sample is the water-table well and women living in Bambe Village and  Randegansari Village. Results : The result of the water-table well examination done on the 30 water-table welsl each village showed that the average cadmium level was 46.73 mg/l in Bambe and  7.93 mg/l in Randegansari. The result of the blood test done on the 30 women each village showed that the average cadmium level was 447.77 mg/l in the women at Bambe and 126.03 mg/l in the women at Randegansari village, the t-test showed with α = 5% there was a significant difference between two village. The average Hb level was 10.60 g/dl l in the women at Bambe and 12.39 g/dl in the women at Randegansari village, the t-test showed with α = 5% there was a significant difference between the two villages. The proteinuria test is done on the 30 women at Bambe village and 30 women at Randegansari village showed  that there were 13 positive, 10 sporce , 7 negative proteinuria  on women in Bambe and 3 positive, 8 spoor, 19 negative on women in Randegansari; by using χ2 test with α = 5% there was a significant difference between the two villages. A multiple linear regression test with α = 5% showed that there was correlation between cadmium level water table-water well, age and blood-cadmium level of women. From the interviewed with the 30 women for each village and using χ2 test with α = 5%, it was found out there were no significant difference in their subjective complaints between women in the Bambe  and women in the Randegansari. Conclusions : Based on the finding of the research it was concluded that there was correlation between cadmium level water table-water well, age and blood-cadmium level of women. Key words: cadmium contamination, water-table well, women health disorders.